(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article examines methods for enhancing legal awareness and legal culture among the population in advanced foreign countries, including Sweden, Germany, the United States, Japan, and Switzerland. Key strategies are analyzed, such as the integration of legal education into curricula, the use of digital platforms, social projects, and collaboration between government bodies and civil society. Special attention is paid to the role of educational institutions, media, and NGOs in fostering legal literacy. The study’s results demonstrate that a combination of mandatory legal education, accessible information resources, and public initiatives contributes to the strengthening of legal culture and the promotion of civic responsibility.